IDENTIFIKASI DAN PENILAIAN RISIKO PETUGAS PENYAPU JALAN RAYA KOTA BALIKPAPAN - Zainul, L.M. Zainul (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
The road sweeper in doing work is very vulnerable with a variety of risks, especially the risk of safety and health such as the risk of hearing loss due to noise, stress, dehydration, getting hit by vehicles, and health disorders due to fatigue, bacterial, impaired respiratory system due to inhaling the smoke of vehicles and dust, or viruses. The purpose of the research is to know the Hazard and risks, to the safety and health of the worker. The research methodology used is a qualitative interface with a cross-sectional design. In conducting identification and risk assessment using Hazard Identification, Risk Assessment and Risk Control (HIRARC), AS/NZS 4360 Standard. The highest risk value (Extreme) is at the hazard of motor vehicles with the risk of being hit by motor vehicles (deceased) 1 (one) category. Total Risk Rating 31 categories with detailed 1 (one) category Extreme, 13 (thirteen) category High, 9 (Nine) Medium category, and category Low as many as 8 (eight) categories.